2020
DOI: 10.1002/ijfe.2032
|View full text |Cite
|
Sign up to set email alerts
|

Financial conservatism, firm value and international business risk: Evidence from emerging economies around the global financial crisis

Abstract: The increase in debt‐free or under‐levered firms (financial conservatism) is one of the most recent stylized puzzles that cannot be explained within the context of extant capital structure theories. In this paper, we exploit the 2008–09 contractions in credit supply in a quasi‐natural experiment to examine whether financial conservatism affects firm value. Using a large sample of firms from seven African countries over the period 2003–2012, we find strong evidence that financial conservatism mitigates the adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Overall, some writers endorsed a perspective motivated by flexibility considerations that financial policies directed at higher cash holdings and conservative debt and payout policies have a "bright face" (e.g. Faulkender and Wang, 2006;Simutin, 2010;de Jong et al, 2012;Rapp et al, 2014;Bliss et al, 2015;Chang et al, 2017;Machokoto et al, 2021). Accordingly, we argue that the value of financial flexibility (VOFF) is a potential mediator that governs the nature of the relationships between these financial policies and firm value.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Overall, some writers endorsed a perspective motivated by flexibility considerations that financial policies directed at higher cash holdings and conservative debt and payout policies have a "bright face" (e.g. Faulkender and Wang, 2006;Simutin, 2010;de Jong et al, 2012;Rapp et al, 2014;Bliss et al, 2015;Chang et al, 2017;Machokoto et al, 2021). Accordingly, we argue that the value of financial flexibility (VOFF) is a potential mediator that governs the nature of the relationships between these financial policies and firm value.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, while uncovering why firms choose a zero-leverage policy, Dang (2013) and Huang et al (2017) found that un-levered firms are motivated by flexibility considerations and financial constraints. Likewise, Machokoto et al (2021) suggested that such a policy alleviates the negative influence of financial constraints on firm value. Instead of following a zeroleverage policy, Cui (2020) argued that small-sized and mature Japanese firms and those with high profitability and low growth prospects tend to hold cash balances that exceed their debt to overcome financial constraints.…”
Section: Corporate Financial Policies and Firm Valuementioning
confidence: 99%
“…The factor receiving the highest average importance rating in both the European and the American polls was "flawed financial sector regulation and supervision" (IGM Forum 2017). 1 The greatest danger to the functionality of the core of the financial system was posed by five systemically large dealers: Bear Stearns, Lehman Brothers, Merrill Lynch, Goldman Sachs, and Morgan Stanley. These investment banks were exceptionally highly leveraged and dependent on flight-prone sources of short-term liquidity.…”
Section: Prone To Fail: the Pre-crisis Financial Systemmentioning
confidence: 99%
“…Admati and Hellwig (2013) argue that the socially excessive and weakly supervised leverage of the largest financial institutions was essentially subsidized by the government through the presumption by creditors that these firms were too big to fail. Creditors apparently assumed that the biggest banks were too important to be allowed by the government to fail, and 1 I was one of those polled. The other factors listed, in order of assessed average importance among all economists, beginning with the second-most important, were: underestimated risks (financial engineering), mortgages (fraud and bad incentives), funding runs (short-term liabilities), rating agency failures, housing price beliefs, household debt levels, too-big-to-fail beliefs, government subsidies (mortgages, home owning), savings and investment imbalances, loose monetary policy, and fair-value accounting.…”
Section: Prone To Fail: the Pre-crisis Financial Systemmentioning
confidence: 99%
“…This propagation of CG codes in emerging markets has coincided with the emergence of emerging market multinational corporations (EMMNCs) with significant operations in both developed and developing countries. Several studies have explored the impact of the unique institutional context of emerging economies on firm's outcomes (Areneke, Yusuf, & Kimani, 2019; Finchelstein, 2017; Machokoto, Areneke, & Nyangara, 2020; Sarhan, Ntim, & Al‐Najjar, 2019; Tunyi, Agyei‐Boapeah, Areneke, & Agyemang, 2019; Wang, Hong, Kafouros, & Wright, 2012; Yaprak, Yosun, & Cetindamar, 2018). The consensus within this literature is that, emerging markets are characterized by poor quality regulations, weak regulatory enforcement, political instability and the presence of corruption – factors that limit the effectiveness of CG regulation within this environment and, potentially, impact on the ability of EMMNCs to compete on the global stage (Bhaumik, Driffield, Gaur, Mickiewicz, & Vaaler, 2019; Nakpodia & Adegbite, 2018).…”
Section: Introductionmentioning
confidence: 99%